2022
DOI: 10.1155/2022/7389258
|View full text |Cite
|
Sign up to set email alerts
|

U-Shape Relationship between Plasma Leucine Level and Mortality in the Intensive Care Unit

Abstract: Patients in the intensive care unit (ICU) are at high risk of mortality which is not well predicted. Previous studies noted that leucine has prognostic value in a variety of diseases. This study investigated whether leucine concentration was a useful biomarker of metabolic and nutritional status and 6-month mortality in ICU. We recruited 454 subjects admitted to ICU (348 and 106 in the initiation and validation cohorts, respectively) with an acute physiology and chronic health evaluation (APACHE II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…It has been shown that leucine levels correlate well with the total amount of essential amino acids [ 18 ]. Recently, we noted a U-shaped relationship between leucine concentrations and ICU mortality [ 17 , 18 ]. High leucine levels represent anabolic resistance and massive endogenous release of energy in the acute phase, characterized by increased unmetabolized acylcarnitines in the circulation due to mitochondrial dysfunction with impaired beta-oxidation [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that leucine levels correlate well with the total amount of essential amino acids [ 18 ]. Recently, we noted a U-shaped relationship between leucine concentrations and ICU mortality [ 17 , 18 ]. High leucine levels represent anabolic resistance and massive endogenous release of energy in the acute phase, characterized by increased unmetabolized acylcarnitines in the circulation due to mitochondrial dysfunction with impaired beta-oxidation [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stress hyperphenylalaninemia has been associated with a three-fold increase of mortality in ICU patients [ 13 , 14 ]. On the other hand, a U-shaped relationship between leucine levels and mortality in ICU patients was also noted [ 17 , 18 ]. High leucine levels may represent large endogenous release of energy and amino acids in the acute phase of critical illness and anabolic resistance, while low leucine levels may imply malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we observed that the frail patients had lower leucine intake compared to the non-frail patients, with higher plasma leucine levels. This might be attributed to the frail patients being in a state of metabolic synthesis resistance, leading to the release of more leucine to overcome the resistance and stimulate muscle protein synthesis [44].…”
Section: Discussionmentioning
confidence: 99%
“…Studied biomarkers are summarized in Table 1, which needs to be interpreted with caution as none of the presented studies is able to provide definitive answers regarding the dynamics and usefulness of putative markers [4 ▪▪ ,20,21,33,34,36 ▪ ,37,39–42,53,54]. Very recently, Jenkins and colleagues have reached similar conclusions regarding both the current absence and the future necessity of biomarkers of GI dysfunction [55 ▪ ].…”
Section: Biomarkers Of the Gut Function In Available Studiesmentioning
confidence: 92%
“…Blood levels of leucine (which is well represented in albumin and prealbumin) appear to have a meaningful correlation with nutritional status, and a new study in 454 ICU patients indicates that an initially high level of this amino acid is an adverse prognostic marker in critical care [36 ▪ ]. A multivariable Cox regression analysis demonstrated that concentrations >174 μM were independently predictive of early mortality after adjusting for age, disease severity and other laboratory markers, while provision of nutrition was not addressed.…”
Section: Biomarkers Of the Gut Function In Available Studiesmentioning
confidence: 99%